Caries dentales asociadas a los hábitos alimenticios en jóvenes y adultos de la Nacionalidad indígena amazónica Zápara. - Peñafiel Carrillo, Esteban Rolando (2024)
Determining the level of dental caries is of utmost importance due to the scarcity of programs in Eastern Ecuador to study and monitor indigenous populations. Likewise, maintaining optimal eating habits is essential for the adequate health of the entire organism. The objective of this study was to analyze the level of dental caries through the application of the DMFT index to establish its link with the eating habits of the Zápara population. The methodology applied was descriptive, cross-sectional, observational, and mixed approach. The study population comprised 31 people of the Zápara nationality following the selection criteria. The results revealed a very high level of caries in the population, with an average DMFT of 10.48, with increasing severity with age. Most participants reported good general eating habits and dietary outlooks, regular cariogenic eating habits, and very good cariogenic eating habits, but a low and negative non-significant relationship between these variables (p = 0.822) (p = 0.787) (p = 0.973). However, a p-value of 0.025 was obtained between the general habits-eating perspective and cariostatic habits. It was concluded that there was no significant statistical association between the level of caries and eating habits. However, a positive, moderate, and significant correlation was found between general eating habits and cariostatic habits.